Respiratory Infections and Vitamin D Supplement Use among Benghazi Infants - Faiza Nouh; Salima Elfagi; Najat Jomaa; Raja Idrees; Esraa Masoud; Heba Naser; Mohamed H Buzgeia (Libyan Journal of Medical and Applied Sciences, 2025)
Several studies link reduced blood 25-hydroxyvitamin D (25(OH) D) levels and high susceptibility to respiratory infection during infancy. Vitamin D has a significant regulatory function in infants' immune system development and respiratory system growth. This study is a cross-sectional study investigates the impact of vitamin D supplement on respiratory infections among infants in Benghazi during winter (2023-2024). 434 subjects have been included in the current study; females and males represent (50.46%) and (49.54%) of the sample respectively. The majority of infants (73.5%) are normal weight, and the majority (70.28%) are normal height. (88.7%) of infants take vitamin D supplements, with the most beginning the supplementation from birth to 4 months (84.3%). The study revealed that 81.8% of the infants were not exposed to the sun directly. The percentage of infants with normal serum vitamin D level is (82.5%). The results of the current study recommend increasing health education and awareness regarding starting vitamin D supplementation as soon as a mother gives birth.